Security and Microservice Architecture on AWS : architecting and implementing a secured, scalable solution - Raje, Gaurav (O'Reilly Media, 2021)
Security is usually an afterthought when organizations design microservices for cloud systems. Most companies today are exposed to potential security threats, but their response is more reactive than proactive. That leads to unnecessarily complicated architecture that's harder to implement and even harder to manage and scale. Author Gaurav Raje shows you how to build highly secure systems on AWS without increasing overhead. Ideal for cloud solution architects and software developers with AWS experience, this practical book starts with a high-level architecture and design discussion, then explains how to implement your solution in the cloud in a secure but frictionless manner. By leveraging the AWS Shared Responsibility Model, you'll be able to: Achieve complete mediation in microservices at the infrastructure level Implement a secure and reliable audit trail of all events within the system Develop architecture that aims to simplify compliance with various regulations in finance, medicine, and legal services Put systems in place that detect anomalous behavior and alert the proper administrators in case of a breach Scale security mechanisms on individual microservices independent of each other.